IMPLEMENTATION OF LEGAL PROTECTION FOR OUTSOURCED LABOR OF KALI BARU PORT STEVEDORING SERVICES COOPERATIVE - Rahman, Abdul; Darwis, Nurlely (JILPR Journal Indonesia Law and Policy Review, 2025)
The Kali Baru Port Stevedoring Services Cooperative (TKBM) is an entity responsible for providing loading and unloading labor at Tanjung Priok Port. Issues such as workplace safety, worker welfare, and social security remain significant challenges. The research questions are: How is legal protection implemented for outsourced workers from the Kali Baru Port Stevedoring Services Cooperative who work at PT New Priok Container Terminal One (NPCT I)? What obstacles are faced in implementing legal protection for outsourced workers of the Stevedoring Services Cooperative at PT New Priok Container Terminal One (NPCT I) Port, and what efforts are being made to overcome these obstacles? This study aims to understand and analyze the implementation of legal protection for outsourced workers from the Kali Baru Port Stevedoring Services Cooperative working at PT New Priok Container Terminal One (NPCT I), and to identify, examine, and analyze the obstacles encountered in providing legal protection for these outsourced workers at PT New Priok Container Terminal One (NPCT I) Port. The research methods employed are juridical normative and juridical empirical. The findings addressing the two research questions indicate that worker protection under the Manpower Law aims to safeguard the fundamental rights of workers. The legal protection in question refers to both preventive and repressive legal protection for outsourced workers. The obstacles to implementing legal protection for outsourced workers at the Kali Baru Port Stevedoring Services Cooperative at PT New Priok Container Terminal One (NPCT I) Port include: human resource competency and quality, working conditions and infrastructure, regulations and institutional frameworks, economic and welfare aspects, and Occupational Safety and Health (K3) awareness and culture. Efforts undertaken to overcome these obstacles include: improving competency and training, enhancing infrastructure and equipment, strengthening regulations and supervision, increasing inter-agency coordination, raising K3 awareness, and improving welfare.